2021
DOI: 10.1017/jfm.2021.350
|View full text |Cite
|
Sign up to set email alerts
|

Stability of sedimenting flexible loops

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…This finding provides an important input to future models of circularised polymers. Incorporating torsional interactions is more difficult than just bending interactions and is often neglected when constructing models of circularized molecules (68, 69, 70, 71). Since the torsional forces play a role even when Δ Lk is close to zero, additional care needs to be taken when generalising such models for the context of supercoiled DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides an important input to future models of circularised polymers. Incorporating torsional interactions is more difficult than just bending interactions and is often neglected when constructing models of circularized molecules (68, 69, 70, 71). Since the torsional forces play a role even when Δ Lk is close to zero, additional care needs to be taken when generalising such models for the context of supercoiled DNA.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the flow far from the body and near the body surface as the SBT asymptotic representations are expected to be the most valid in these regions. We found that any line of regularized Stokeslets can approximate the flow far from the body provided that the regularization parameter, , is equal to the thickness of the body, aρ 0 , multiplied by a constant that depends on the regularization blob, (8π ∞ 0 u 4 f (u) du/3) −1/2 , Equation (23). This constant can be used for the unknown proportionality constant used in numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, SBTs have been divided into two types: those that expand the system in powers of 1/ ln(a) [1,3] and those that expand the system in powers of a [4][5][6][7]. The former is often called resistive force theory and provides useful analytical estimates [17][18][19][20][21][22][23][24], while the latter has been shown to provide highly accurate results in numerous situations [11][12][13][14][15][16].…”
Section: Classical Slender-body Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The form of the integral operator in nonlocal slender body renders the dynamic problem for the curve evolution much more difficult. Using resistive force theory for the force-to-velocity map along the fiber simplifies the curve evolution problem while still remaining relevant from a current modeling perspective (see, for example, [1,4,5,6,30,43,46,52,60,63]).…”
Section: Introductionmentioning
confidence: 99%